0364 Sex and Race Influence Objective and Self-Report Sleep and Circadian Measures in Emerging Adults at Risk for Bipolar Spectrum Disorder. (27th May 2020) - Titone, M K; McArthur, B; Ng, T H; Burke, T A; McLaughlin, L E; MacMullen, L E; Alloy, L B; Goel, N
Abstract: Introduction: There is a critical need to understand key factors that impact sleep and circadian rhythm function for emerging adults at risk for bipolar spectrum disorder (BSD). Sex and race are common demographic factors contributing to differences in health outcomes; however, the influence of these variables on sleep and circadian rhythm patterns for emerging adults at risk for BSD has not been characterized. Methods: Multiple objective and self-report facets of sleep and circadian function, including dim light melatonin onset (DLMO), and measures derived from actigraphy and sleep diaries, were assessed in a 20-day ecological momentary assessment (EMA) study of 150 emerging adults (mean ± SD, 21.8 ± 2.1y; 58.7% female; 57.9% White, 23.4% Black, 10.3% Asian or Pacific Islander, 8.0% Other ethnicity) at-risk for BSD. Bivariate Pearson correlations (two-tailed, p <.05) were conducted between the sleep and circadian measures. ANCOVAs, controlling for BSD status, were conducted to evaluate differences on sleep and circadian characteristics by sex and race. Results: Males exhibited better actigraphic sleep efficiency and later DLMO phase than females, whereas females exhibited more actigraphic discrete sleep periods. White participants exhibited more actigraphy-measured total sleep time, better sleep efficiency, and fewer sleep periods, and self-reported more total sleep time and better sleep efficiency than Black participants. Conclusion: We show for the first time that sex and race are significant predictors of objective and self-reported sleep and circadian rhythm measures in a large sample of emerging adults at risk for BSD participating in an EMA study. Our findings extend the existing literature to a novel clinical population and to a naturalistic setting and inform ongoing research on sex and racial health disparities in sleep and circadian rhythms. Support: This work was supported by NIH R01 MH77908 and R01 MH102310; a Banting Postdoctoral Fellowship from the Social Sciences and Humanities Research Council; and a National Science Foundation Graduate Student Research Fellowship.